Adiposity affects emotional information processing - Romero-Rebollar, César; García-Gómez, Leonor; Báez-Yáñez, Mario G.; Gutiérrez-Aguilar, Ruth; Pacheco-López, Gustavo (Frontiers in Psychology, 2022)
Obesity is a worldwide epidemic associated with severe health and psychological well-being impairments expressed by an increased prevalence of affective disorders. Emotional dysfunction is important due to its effect on social performing. The aim of the present narrative review is to provide a general overview about human research exploring emotional information processing in obesity and overweight. Evidence suggests that obesity is associated with an attenuation of emotional experience, contradictory findings about emotion recognition, and scarce research about automatic emotional information processing. Finally, we made some concluding considerations for future research on emotional information processing in overweight and overweight.